PENGARUH HARGA TERHADAP LOYALITAS PELANGGAN TRANSPORTASI ONLINE INDRIVE DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Vira Farida; Putri Hestiningrum (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
This study aims to determine the effect of price on customer loyalty among InDrive online transportation users in Surabaya and to determine the role of customer satisfaction as a mediating variable in the relationship between price and customer loyalty. The type of research used is causal with a quantitative approach. The sample used is InDrive online transportation users in Surabaya City with an age range of 15-59 years who have used InDrive at least 2 times. The sampling technique used a purposive sampling technique with a sample size of 115 respondents. The data analysis technique used is Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPls software. The results of the study indicate that price affects customer satisfaction, customer satisfaction affects customer loyalty, price does not affect customer loyalty. Other findings indicate that price affects customer loyalty through customer satisfaction.